Large plaque parapsoriasis in a child: A rare entity in pediatric oncology - Bahareh Abtahi-Naeini; Farahnaz Fatemi Naeini; Mohammad Faranoush; Najmeh Bolandnazar (Indian Journal of Medical and Paediatric Oncology)
Parapsoriasis is exceedingly rare in children. The presentation, course, and prognosis of parapsoriasis in children have not yet been completely elucidated. Here, a case of large plaque parapsoriasis in 10-year-old boy is reported who was diagnosed recalcitrant pediatrics eczema for about 5 years. Other clinicians had previously treated him with emollients and topical corticosteroids with temporary relief but without improvement. The erythematous scaly patches were situated on the trunk and flank. On skin biopsy, the lymphocytic infiltrate was composed mainly of CD4+ and CD45RO+ lymphocytes. No T-cell receptor gene rearrangements were found. The paucity of knowledge about the evolution of this entity in childhood and its relationship to mycosis fungoides makes follow-up critical.